2016
DOI: 10.1002/2016ja022697
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of IRI and IRI‐Plas models over the African equatorial and low‐latitude region

Abstract: A reliable ionospheric specification by empirical models is important to mitigate the effects of the ionosphere on the operations of satellite‐based positioning and navigation systems. This study evaluates the capability of the International Reference Ionosphere (IRI) and IRI extended to the plasmasphere (IRI‐Plas) models in predicting the total electron content (TEC) over stations located in the southern hemisphere of the African equatorial and low‐latitude region. TEC derived from Global Positioning System (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…(2018) compared the performance of IRI-Plas with other ionospheric models such as the IRI and NeQuick-2 models in the African region. In Adebiyi et al., 2016a, Adebiyi et al., 2016b, the predictions of the IRI-Plas and the three topside options of the IRI models were found to show latitudinal and seasonal trends. In other words, IRI-Plas model was found to perform better than the IRI in months and seasons where the IRI model underestimates TEC.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…(2018) compared the performance of IRI-Plas with other ionospheric models such as the IRI and NeQuick-2 models in the African region. In Adebiyi et al., 2016a, Adebiyi et al., 2016b, the predictions of the IRI-Plas and the three topside options of the IRI models were found to show latitudinal and seasonal trends. In other words, IRI-Plas model was found to perform better than the IRI in months and seasons where the IRI model underestimates TEC.…”
Section: Introductionmentioning
confidence: 98%
“…Studies to validate the IRI model at different regions have been conducted by different authors e.g. Adebiyi et al., 2014; Adebesin et al.,2014; Adebiyi et al., 2016a, b; Grynyshyna-Poliuga et al.,2015; Scidá et al., 2012, Olawepo et al., 2017 etc. Results from some of these studies have revealed discrepancies in the performance of the model, some of which have been attributed to its inability to account for the plasmaspheric contribution to the ionospheric total electron content (TEC) e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Tariku (2019) noted that none of the versions of the IRI model are able to adequately estimate the variation of the VTEC over the equatorial and low latitude region (Ethiopia). Moreover, Adebiyi et al (2016), Ezquer et al (2017) and Zakharenkova et al (2015) discussed that the IRI‐Plas 2015 model generally showed overestimations as compared to the IRI 2012 model over the African equatorial and magnetic low latitude regions. Okoh et al (2018) also noted that the NeQuick 2 model tends to underestimate the VTEC variations during the high solar activity years.…”
Section: Introductionmentioning
confidence: 99%
“…The IRI model (and the IRI‐Plas as one of the extensions to the plasmasphere) has been reinstated by ISO (ISO 16457:2014) as given in https://www.iso.org/standard/61556.html in 2014. It has been shown in the literature that the assimilation of TEC into the model improves the representation of current ionospheric state significantly (Adebiyi et al, , ; Bolaji et al, ; Ezquer et al, ; Maltseva et al, , ; Panda et al, ; Zakharenkova et al, ). The IRI‐Plas model is available at http://ftp.izmiran.ru/pub/izmiran/SPIM/ as a FORTRAN code.…”
Section: Introductionmentioning
confidence: 99%